PANDANGAN AL-QUR'AN TENTANG SOLUSI PENGENTASAN KEMISKINAN KELUARGA DAN MASYARAKAT MUSLIM MELALUI PENDEKATAN TAFSIR TEMATIK - S, Samsidar; Sohra, Sohra; Mujahid, Ahmad (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
This research aims to reveal the Al-Qur'an's views on solutions to poverty alleviation in Muslim families and communities, by identifying and classifying Al-Qur'an verses that discuss poverty and solutions to its alleviation in the contemporary era. The research method used is a literature study with secondary data sourced from verses of the Al-Qur'an and their interpretations, using a descriptive analytical approach. In the discussion it was revealed that the Qur'an offers several concrete and holistic solutions in overcoming poverty, which includes economic, social and spiritual aspects, including: Implementation of the zakat, infaq and alms and waqf systems as a means of economic equality and philanthropy in Islam, In this way, there will be an integration of spiritual and material aspects in alleviating poverty. The application of Al-Qur'an solutions in alleviating poverty starts from the individual, family, community level, up to the state level as a policy regulator.